ACCORDING TO THE TURKISH REPUBLIC ARCHIVES THE FOREIGNER’S ASPECTS ON TURKEY’S CYPRUS POLICY (1955-1959) - Hikmet Zeki KAPCI (Fırat University, 2019)
The Cyprus Question is a problem of Turkey that continued for years. Cyprus was conquered in 1878 by England that continuing to obtain colonies all around the world in the 19th century. Cyprus is one of the dominions of the Great Britain after the Lozan Treaty of Peace. However, the Greek Cyprus began to struggle to gain independence from Britain since 1931. After this Turkey did not think to interfered to Cyprus. The Great Britain change her policy after the World War II. And she started to go out her dominion territories slowly. Therefore the influence war beginned on Cyprus between Turkey and Greece. As well Turkey has started to be included in the Cyprus problem since 1950. The period of the Democratic Party has been the Cyprus problem one of the most important foreign policy issues. Turkey is not go into struggle on Cyprus that the Great Britain remains her control. Turkey thinks that if England wants to go out from Cyprus then has a right to say on Cyprus. Because Cyprus is very close to Turkey for geographical and historical. At this moment there was a serious and heavy competition on Cyprus between Turkey and Greece. Turkey’s aim was not to persecuting the Cyprus Turks’ from other states. If England went out from Cyprus it was not thought a solution without Turkey. And so Turkey began to take a step on this policy. But Turkey never followed complicate comprehension. Şhe followed genial policy. Especially, After the London Conference, Turkey has become officially part of the subject. Turkey has primarily want to continue the status quo. If this is not, it has argued the entire island should be given its. The